TEACHING MATHEMATICS WITH PIAGET'S THEORY - Ega Gradini (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2013)
Piaget's theory of cognitive development is a comprehensive theory about the nature and development of human intelligence first developed by Jean Piaget. It is primarily known as a developmental stage theory, but in fact, it deals with the nature of knowledge itself and how humans come gradually to acquire it, construct it, and use it. Moreover, Piaget claims the idea that cognitive development is at the centre of human organism and language is contingent on cognitive development. Below, there is first a short description of Piaget's views about the nature of intelligence and then a description of the stages through which it develops until maturity.This paper presented student’s way of thinking in mathematics learning. Jean Piaget’s theory brought here as the main concept applied on children thinking process in mathematics. Through observation, some fact emerges in every stage of development process. Those display on “Cant and But Can’t” Table.